Mitigasi Risiko Produksi Bibit Anggur dengan Teknik Penyambungan (Grafting) di Arga Urban Farming Jakarta Selatan - Yuni Sulistyowati (Department of Agribusiness, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2026)
This research aims to (1) Identify risks in grape seedling production activities using grafting techniques in Arga Urban Farming, (2) Measure the level of risk in grape seedling production activities using grafting techniques in Arga Urban Farming, (3) Map the risks of grape seedling production using grafting techniques in Arga Urban Farming, and (4) Recommend risk mitigation and priorities that can be applied to control risks in grape seedling production activities using grafting techniques in Arga Urban Farming. The data used in this study use primary data obtained through observation, interviews, and filling out questionnaires. The analysis tools used in this study include HOR (House of Risk) and Pareto diagrams. Based on this study, 18 risk events and 24 risk causes were obtained in the entire series of grape seedling production processes in Arga Urban Farming. Based on the results of identifying appropriate risk mitigation through calculations on HOR phase 1 and risk mapping using the Pareto diagram, there are 10 priority risk causes (2 in the grafting process, 5 in the maintenance process, 1 in the sorting process, and 2 in the packaging process). To handle these priority risk causes, 20 mitigation actions need to be carried out in the grape seedling production process at Arga Urban Farming